HUBUNGAN PERCEIVED RISK DAN SELF CONCEPT DENGAN BRAND LOYALTY PADA KONSUMEN PRODUK KOSMETIK - Kentjana, Noella (University of Surabaya, 2016)
The purpose of this study is to see the relationship between perceived risk and self concept with brand loyalty in consumer cosmetic products. The subject in this study is 307 college student at the University of Surabaya from 18 to 25 years in accordance with the period development of emerging adults. Result in the study show there is a relationship between perceived risk and self concept together with the brand loyalty of cosmetic product (F= 111,21; p 0,05),there is a relationship between perceived risk with brand loyalty (r = -0,633; p< 0,05), there is a relationship between self concept with brand loyalty (r= 0,339; p=<0,05). Based on the study, an increase of brand loyalty can occur when consumers cosmetic products have low perceived risk an their self concept is high. To increase brand loyalty, manufacturers must consider the perceived risk and self concept of their consumer because brand loyalty is one way to keep and maintain customer.